Implementacja controllingu do zarządzania wyższą uczelnią - Parkitna, Agnieszka (The Implementation of Controlling in Management of Educational Institutions at University Level, 2008)
The author presents the essence of controlling and the premises of its using in management of educational institutions at university level. The reasons for the lack of proper use of controlling type of institutions were shown. Rules for implementing controlling were discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 403-410